PERANCANGAN SISTEM CHATBOT SEBAGAI VIRTUAL ASSISTANT PADA PT. EVERBRIGHT JAMBI - Almustaqim, Andry; Toscany, Afrizal Nehemia (Universitas Budi Luhur, 2022)
The use of Artificial Intelligence in many businesses in Indonesia has been increased because of the flexibility that the system offers. One of the implementations of AI is a chatbot, which is used as a virtual assistant in a company to provide better quality customer service. In this research, we demonstrate how to create a chatbot that can be used as a virtual assistant in PT. EVERBRIGHT Jambi in order for the company to present better customer care. Moreover, the bot is being built using Natural Language Processing, in which enables the bot to understand human languages. By integrating the chatbot, the company will be able to provide 24-hour-a-day customer service without having the need to spend more cost on this. We are building the chatbot using Python and JSON. Furthermore, the system will be deployed in the Application Programming Interface called Telegram. Based on the result of the test conducted using the Black Box method, the chatbot has the ability to reply within seconds and the answers are about 85 percent accurate. As a result, the chatbot is capable of giving sufficient information to the customer based on the data that has been previously given to train the bot.